The administrative presidency as reactive oversight: implications for positive and normative theory - West, William F. (2015)
The fact that centralized executive oversight of agency policy making is primarily reactive reflects the motives and constraints that define the president's relationship with the domestic bureaucracy. Such a strategy allows for the allocation of limited resources to agency initiatives that are inconsistent with the president's agenda or that evoke conflict within the executive branch or the larger political system. This calls into question the descriptive model of presidential administration as proactive management by a unitary actor, as well as its prescriptive corollary that equates a strong executive with coordination across the bureaucracy. Reactive presidential oversight can produce a kind of ad hoc coordination that can be salutary, but its often pluralistic character can also undermine other important values in the administrative process. - Reproduced.
Keywords: Public administration